GAYA ANGKAT DAN GAYA HAMBAT SAYAP PUNA MODEL NACA 0015 MENGGUNAKAN SIMULASI ANSYS FLUENT - Dzulfikar, Muhammad; Purwanto, Helmy; Abdul Wahid, Muhammad; Rahmatulloh, Salim (Jurnal Rekayasa Mesin, 2024)
The hi-speed computational using simulation software has emerged for the calculation of force dynamic. Albeit the significant progress in the computational method, the aerodynamic of flying wing are somewhat elusive. Herein, we performed a detailed computation of the lift and drag behaviors of NACA-0015 flying wing modelled through the surveillance speeds and difference angle of attack using Ansys. This study aims to determine and analyze the maximum angle of attack, lift force and drag force at speeds of 10 m/s, 30 m/s, and 50 m/s. The method used is analysis using CFD (Computational Fluid Dynamic) simulation software. The simulation uses Ansys Fluent to determine the aerodynamic characteristics, after varying the angle of attack at a predetermined speed on an airplane (unmanned aerial vehicle) wing with a NACA 0015 airfoil. The results of the research that has been carried out are the maximum angle of attack at a predetermined speed variation (Re = 0.2 x 105 to 1.0 x 105), namely 25° at each angle of attack, with details of a speed of 50 m/s getting the highest lifting force, around 38,72 N and drag force in the area 6,49 N.